The formation of a host‐guest inclusion complex system between β‐cyclodextrin and baicalin and its dissolution characteristics. (16th March 2017) - Li, Jing; Jiang, Qihua; Deng, Ping; Chen, Qian; Yu, Mingan; Shang, Jingchuan; Li, Wei
Abstract: Objectives: Baicalin (BCL) has potential therapeutic benefits, but its clinical outcomes are restricted mainly because of low water solubility. This study sought to improve the water solubility of BCL by the formation of inclusion complex with β‐cyclodextrin (β‐CD). Methods: The inclusion complex was studied by solubility test, differential scanning calorimeter (DSC), Fourier transform infrared spectroscopy (FTIR), X‐ray diffraction (XRD), 1 H Nuclear magnetic resonance ( 1 HNMR) and scanning electron microscopy (SEM). Molecular docking was conducted to verify the experimental findings. The dissolution rate was determined by dialysis membrane method. In vivo absorption studies in rats were conducted and high‐performance liquid chromatography (HPLC) was used to analyse the plasma level of BCL after oral administration. Key findings: The DSC, FTIR, XRD, 1 HNMR and SEM findings suggested the formation of inclusion complex between BCL and β‐CD in 1 : 1 stoichiometry. Molecular docking demonstrated the insertion of benzene ring of BCL into β‐CD cavity by hydrophobic interactions and possible H‐bond formation. Moreover, β‐CD markedly improved the solubility of BCL and displayed AL ‐type phase diagrams. The improvement in dissolution rate of the inclusion complex was reflected in the earlier T max, higher C max and larger AUC0– t than that of BCL after oral administration. Conclusions: β‐cyclodextrin complex can be used as an effective formulation strategy for development of BCL‐loaded delivery system with better therapeutic outcomes.